Chemical analysis qualitative and quantitative : laboratory practices and seminaries of analytical chemistry - Mikuš, Peter; Mikušová, Veronika (Comenius University in Bratislava, 2011)
This book deals with the traditional analytical methods known as the chemical analysis. Although the modern instrumental methods play now the key role in most of the application areas including pharmaceutical and biomedical analysis, chemical analysis has the definite position in a proper understanding of the chemistry of analytical reactions and mutual interactions of various chemical systems. In this way, the student can obtain correct view of the work in the analytical laboratory, basic habits and skills. Moreover, the student learns to think on the problems analytically what can be utilized when solving various advanced problems in the analytical laboratory but also in real life. The aim of this book is to provide the pharmacist with a compact view on themethods of chemical analysis. Although there are not included all existing methods and examples in this text, the whole area of the chemical analysis is covered by the carefully selected representative examples of the methods suitable for the pharmacist.